IInitiative Budgeting in Central Asia and Transcaucasia: Prerequisites and Trajectories - Vladimir V. Vagin; Irina V. Petrova; Mikhail V. Kurakolov (Финансовый журнал)
The article explores the experience of introducing initiative budgeting in a number of Central Asian and Transcaucasian countries. It analyzes citizens’ involvement in the process of budgetary decision-making and defines the regulatory, financial, and organizational characteristics of the emerging management structure for this financial innovation. Effective participation of citizens contributes to the formation of more balanced and equitable budgets that reflect the actual needs of society. The development of initiative budgeting in the Republic of Uzbekistan is characterized as dynamic, with a special emphasis on modernization and digitalization of civic engagement processes, allowing a significant part of the population to actively participate in determining the priorities of state budget expenditures. In the Kyrgyz Republic, this approach has proven highly effective at the level of local authorities, where citizens actively influence the allocation of limited resources, thereby improving the quality of life in their communities. The financial authorities of the Republic of Armenia consider initiative budgeting as a means of enhancing public confidence in the government and the efficiency of budgetary resource allocation. The Republic of Kazakhstan, in turn, focuses on the adoption of advanced technologies to increase transparency and accessibility of budgetary data for a wide audience. In most Central Asian and Transcaucasian countries, the key role in the development of initiative budgeting is played by financial authorities at both national and local levels. This article will be of interest to researchers specializing in budgetary and financial trends and civic engagement in these regions.